Quality determination of the Saudi retail banking system and the challenges of Vision 2030 - Mohammad Ishfaq; Heitham Al-Hajieh; Majed Alharthi (International Journal of Financial Studies, 2020)
Vision 2030 of the Kingdom of Saudi Arabia (KSA) requires numerous national and multinational organizations to re-engineer themselves to achieve the required targets for the upturn of the Saudi economy. In this respect, the quality of indigenous goods and services has been the biggest challenge to satisfy consumers of Saudi businesses. The banking and finance sector, specifically, has a great deal of responsibility to put in place a strong financial system that is capable of attracting capital from both local and foreign investors. SERVQUAL, with the five conventional dimensions-tangibility, reliability, responsiveness, assurance and empathy-offers a great deal of flexibility in modifying the model to the specific requirements of a service in carrying out gap analysis. In this context, we have applied SERVQUAL by adding two new dimensions-functional and technical-to the conventional five dimensions. We applied SERVQUAL using a "performance-only approach" to identify quality gaps present in the services of national and multinational banks. Our analysis shows that gaps exist in the service quality-both in national and multinational banking systems. We therefore present weighted gap scores to assist service managers in setting up priorities to improve the quality of their services. This study suggests that there is much to be done to improve retail banking quality and gain customers' confidence, both from within and outside the KSA.
Keywords: 330; SERVQUAL; Saudi Arabian retail banking system; KSA Vision 2030